Room-temperature biosynthesis of ferroelectric barium titanate nanoparticles - Bansal, Vipul; Poddar, Pankaj; Ahmad, Absar; Sastry, Murali (Journal of the American Chemical Society, 2006)
The syntheses of inorganic materials by biological systems is characterized by processes that occur close to ambient temperatures, pressures, and neutral pH, as is exemplified by biosilicification and biomineralization processes in nature. Conversely, laboratory-based syntheses of oxide materials often require extremes of temperature and pressure. We have shown here the extracellular, room-temperature biosynthesis of 4-5 nm ternary oxide nanoparticles such as barium titanate (BT) using a fungus-mediated approach. The tetragonality as well as a lowered Curie transition temperature in sub-10 nm particles was established, and the ferroelectricity in these particles was shown using Kelvin probe microscopy.